2020
DOI: 10.3390/jcm9041088
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Redistribution of Peripheral Lymphocyte Subpopulations after Switching from Calcineurin to mTOR Inhibitors in Kidney Transplant Recipients

Abstract: Classical immunosuppression based on steroids, calcineurin inhibitors, and mycophenolate results in several unwanted effects and unsatisfactory long-term outcomes in kidney transplantation (KT). New immunosuppressors search for fewer adverse events and increased graft survival but may have a distinct impact on graft function and immunological biomarkers according to their mechanism of action. This prospective study evaluates the immunological effect of tacrolimus to serine/threonine protein kinase mechanistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 64 publications
1
1
0
Order By: Relevance
“…Consistently, studies demonstrated inhibition of proliferation and induction of apoptosis of Th cells as well as a selectively expansion of Treg upon mTORi treatment in vivo or in vitro. [22][23][24] In line, we here demonstrated a suppression of p70S6K phosphorylation in CD4 + CD45RA -CD25 − Th cells by mTORi, while CD4 + CD45RA -CD25 ++ CD127 − Treg remained unaffected. The latter reflect their independence from mTOR signaling (Figure 4).…”
Section: Discussionsupporting
confidence: 83%
“…Consistently, studies demonstrated inhibition of proliferation and induction of apoptosis of Th cells as well as a selectively expansion of Treg upon mTORi treatment in vivo or in vitro. [22][23][24] In line, we here demonstrated a suppression of p70S6K phosphorylation in CD4 + CD45RA -CD25 − Th cells by mTORi, while CD4 + CD45RA -CD25 ++ CD127 − Treg remained unaffected. The latter reflect their independence from mTOR signaling (Figure 4).…”
Section: Discussionsupporting
confidence: 83%
“…For example, FK-506 is often treated with MMF in kidney transplantation. Based on individual differences, other treatment regimens include FK-506/EVR/prednisolone (Perd), FK-506/mycophenolic acld (MPA)/Perd triple regimens, and FK-506/EVR double regimens [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%